Confirmation of the mantle-cell lymphoma International Prognostic Index in randomized trials of the European Mantle-Cell Lymphoma Network - Hoster, Eva; Klapper, Wolfram; Hermine, Olivier; Kluin-Nelemans, Hanneke C; Walewski, Jan; van Hoof, Achiel; Trneny, Marek; Geisler, Christian H; Di Raimondo, Francesco; Szymczyk, Michal; Stilgenbauer, Stephan; Thieblemont, Catherine; et al. (Journal of clinical oncology, 2014)
PURPOSE: Mantle-cell lymphoma (MCL) is a distinct B-cell lymphoma associated with poor outcome. In 2008, the MCL International Prognostic Index (MIPI) was developed as the first prognostic stratification tool specifically directed to patients with MCL. External validation was planned to be performed on the cohort of the two recently completed randomized trials of the European MCL Network. PATIENTS AND METHODS: Data of 958 patients with MCL (median age, 65 years; range, 32 to 87 years) treated upfront in the trials MCL Younger or MCL Elderly were pooled to assess the prognostic value of MIPI with respect to overall survival (OS) and time to treatment failure (TTF). RESULTS: Five-year OS rates in MIPI low, intermediate, and high-risk groups were 83%, 63%, and 34%, respectively. The hazard ratios for OS of intermediate versus low and high versus intermediate risk patients were 2.1 (95% CI, 1.5 to 2.9) and 2.6 (2.0 to 3.3), respectively. MIPI was similarly prognostic for TTF. All four clinical baseline characteristics constituting the MIPI, age, performance status, lactate dehydrogenase level, and WBC count, were confirmed as independent prognostic factors for OS and TTF. The validity of MIPI was independent of trial cohort and treatment strategy. CONCLUSION: MIPI was prospectively validated in a large MCL patient cohort homogenously treated according to recognized standards. As reflected in current guidelines, MIPI represents a generally applicable prognostic tool to be used in research as well as in clinical routine, and it can help to develop risk-adapted treatment strategies to further improve clinical outcome in MCL.
Keywords: senioři; proporcionální rizikové modely; Proportional Hazards Models; Doxorubicin; multicentrické studie jako téma; cyklofosfamid; senioři nad 80 let; prednison; Cytarabine; Prognosis; Multicenter Studies as Topic; Cohort Studies; myší monoklonální protilátky; Cisplatin; Middle Aged; Peripheral Blood Stem Cell Transplantation; cisplatina; mužské pohlaví; transplantace periferních kmenových buněk; chemoradioterapie; Adult; Vincristine; kohortové studie; Lymphoma, Mantle-Cell; Aged, 80 and over; Neoplasm Staging; Rituximab; doxorubicin; ženské pohlaví; prognóza; Cyclophosphamide; Humans; Randomized Controlled Trials as Topic; Prednisone; cytarabin; dexamethason; Antibodies, Monoclonal, Murine-Derived; rituximab; lidé středního věku; vinkristin; Antineoplastic Combined Chemotherapy Protocols; staging nádorů; protokoly protinádorové kombinované chemoterapie; Dexamethasone; dospělí; randomizované kontrolované studie jako téma; Female; Aged; Chemoradiotherapy; lidé; Male; lymfom z plášťových buněk